2017
DOI: 10.1002/ajhb.22964
|View full text |Cite
|
Sign up to set email alerts
|

Equation‐derived body fat percentage indicates metabolic abnormalities among normal‐weight adults in a rural Chinese population

Abstract: Our study suggested that high BF% based on equations may indicate adverse metabolic profiles among rural Chinese adults with a normal BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Secondly, when classifying subjects by their TBF% diagnosis, it was clear that CSD consumption is significantly higher in men with a high TBF% diagnosis; also, when the classification was done with the quartiles of CSD consumption, those men with the highest consumption present a significantly higher TBF%, and finally the regression model revealed that CSD consumption was predictive of TBF%. An increase in TBF% per se has been associated with metabolic abnormalities [44,45], for which we can state that a high consumption of CSDs represents a metabolic risk factor, especially because the CSD consumption predicts the TBF% in those young men that participate in our study, and this result is more alarming if we consider that these measures are likely to increase when the subjects reach their 40s [46,47].…”
Section: Discussionmentioning
confidence: 78%
“…Secondly, when classifying subjects by their TBF% diagnosis, it was clear that CSD consumption is significantly higher in men with a high TBF% diagnosis; also, when the classification was done with the quartiles of CSD consumption, those men with the highest consumption present a significantly higher TBF%, and finally the regression model revealed that CSD consumption was predictive of TBF%. An increase in TBF% per se has been associated with metabolic abnormalities [44,45], for which we can state that a high consumption of CSDs represents a metabolic risk factor, especially because the CSD consumption predicts the TBF% in those young men that participate in our study, and this result is more alarming if we consider that these measures are likely to increase when the subjects reach their 40s [46,47].…”
Section: Discussionmentioning
confidence: 78%
“…At the end of the search process, we amassed a total of twenty-four cross-sectional studies, 13,14,18,22,23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] comprising a total of 75 201 patients, which were included in the qualitative synthesis (Figure 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…In this meta-analysis of 24 cross-sectional studies, the prevalence of NWO in the normal weight population was 8104 out of 75 201 (10.8%). 13,14,18,22,23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] South Asia had the highest prevalence of NWO (30%) followed by South America (19.5%), southeast Asia (18%), East Asia (11%), Europe (9.7%) and United States (9%). 13,14,18,22,23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Regarding anthropometric measurement, the meta-analysis showed that NWO subjects were associated with higher BMI (MD 1.74 [1.57, 1.9]; p < .001; I 2 = 85%, P heterogeneity < 0.001).…”
Section: Population Characteristics In Nwomentioning
confidence: 99%
“…In a Chinese hypertension registry study, BFP was found to be positively associated with an increased risk of HUA among hypertensive patients ( 35 ). BFP was also found to be associated with cardiometabolic disorders in a variety of populations ( 36 , 37 ). Excess body fat increases morbidity, with excess visceral fat being an important factor that triggers pathologies among cardiometabolic risk factors ( 38 41 ).…”
Section: Discussionmentioning
confidence: 99%